The Relationship between Self-Compassion, Social Connectedness and Depressive Symptoms among University Students - Muddsar Hameed; Grana Bangash; Maryam Mohsin; Muhammad Ali Hassan; Museera Aymen (Journal of Management Practices, Humanities and Social Sciences, 2023)
The purpose of this research is to examine and explore the affiliation between Self-compassion, social connectedness and Depressive symptoms among university students belonging to the age group of 18-25 years. The research study was cross-sectional in design. This study was conducted in Shifa Tameer-e-Millet University, Rawalpindi/Islamabad. The duration of the study was from October 2021 to September 2022. Quaid-e-Azam University, International Islamic University, Arid Agriculture University, Bahria University, NUST, and Air University were among the universities in Islamabad from which the data was gathered. A survey was conducted to collect data from different universities of Islamabad. 215 students participated in this study among which 52% percent were females and 48% were males. The three measures used in this study were Social Connectedness scale-revised (SCS-R), Self-Compassion Scale Short Form (SCSSF) and lastly, Centre for Epidemiologic Studies Depression Scale-Revised (CESD-R). The research findings showed that self-compassion and Social connectedness have a significant and negative relationship with depressive symptoms. Moreover, the findings depicted that Social connectedness had a significant and positive relationship with Self Compassion. The research findings demonstrated social connectedness and self-compassion have a negatively significant relationship with the depressive symptoms. The results of t-test analysis showed that depression was more prevalent in female population than in males. This study concluded that self-compassion and social connectedness decreases depressive symptoms and social connectedness increases self-compassion. It also concluded that females are vulnerable to depressive symptoms.The findings suggest that fostering self compassion and enhancing social connectedness could potentially contribute to reducing depressive symptoms in this demographic. Additionally, recognizing the higher vulnerability of females to depressive symptoms underscores the importance of gender-sensitive mental health interventions.